Ethnomedicinal Knowledge of the Contemporary Maasai Community in Kenya - Kamau, L. (Africa Environmental Review Journal, 2020)
In this study, plant uses and knowledge of medicinal plants species among the Maasai Community in Kenya were evaluated. Traditional practitioners from Narok County willing to participate in the study were selected. Data was collected through interviews; field observations and administration of close and open ended, semi-structured questionnaires. It aimed at collecting comprehensive ethnotherapeutic information. The data was analyzed using descriptive statistics, some responses were quoted verbatim. A total of 27 ailments and conditions were mentioned; most cited communicable disease included; stomach ache (11.7%) and non-communicable included, heart burn (5.8). Ailments were treated using several herbs individually or in combination. A total of thirty-five plants distributed in 26 families and 35 genera were documented. The wide ethnobotanical knowledge revealed in this study pointed at the importance of traditional medicine in managing health in the face of escalating costs of conventional medicine and growing number of diseases resistant to modern medicine. The study concluded that the present Maasai herbal practitioners had exceptional broad understanding of medicinal plants used in the treatment of various diseases affecting members of their community. The study further recommended efficacy studies of the documented medicinal plants.